ENGINEERING OF SELECTED PROPERTIES OF LIGHT MEDIUM DENSITY FIBREBOARDS PRODUCED FROM HARDWOOD TREE SPECIES (Innovation in Woodworking Industry and Engineering design, 2026)
In this paper are presented results from study for the influence of hot-pressing temperature and press factor on some properties of light Medium Density Fibreboards (MDF) from hardwood tree species. MDF were produced from under laboratory conditions with phenol-formaldehyde resin as binder. The press factor varied from 45 to 90 s.mm-1 and the hot-pressing temperature was from 150° to 190 °C.For the engineering of selected properties of the boards were applied the methods of regression analyze. Experimentally-statistical models that describe the studied relations and the optimal values of the factors were deduced. It has been established that by adjustment of the studied factors the properties of MDF from hardwood tree species can be significantly improved. It was also found that in the studied range, the temperature of hot pressing has a significantly greater influence on properties of MDF than the press factor.